Mechanism of Governance of Economic Relations - Rus, Andrej (Teorija in Praksa, 2012)
The problem of the governance of economic transactions arises from the fact that they are sequential. This creates uncertainty regarding the fulfilment of implicit or explicit contracts. Institutional economics understands this uncertainty as arising from opportunism and seeks a solution in specialised contract enforcement institutions. Economic sociology understands the uncertainty as a result of misunderstanding and finds a solution in mechanisms of governance that, in addition to sanctions, allow for coordination among participants in a transaction. In this paper, we confront the arguments made by sociology and economics regarding the mechanism of governance of economic transactions. Following Polanyi, we distinguish three governance mechanisms of economic relations and note that, to be operational, each of them requires a different social structure and social regulation.
Keywords: economic activity; economic sociology; economics; governance mechanisms; institutional economics; social structure; socioeconomics

Mehanizmi Upravljanja Ekonomskih Odnosov - Rus, Andrej (MECHANISM OF GOVERNANCE OF ECONOMIC RELATIONS., 2012)
The problem of the governance of economic transactions arises from the fact that they are sequential. This creates uncertainty regarding the fulfilment of implicit or explicit contracts. Institutional economics understands this uncertainty as arising from opportunism and seeks a solution in specialised contract enforcement institutions. Economic sociology understands the uncertainty as a result of misunderstanding and finds a solution in mechanisms of governance that, in addition to sanctions, allow for coordination among participants in a transaction. In this paper, we confront the arguments made by sociology and economics regarding the mechanism of governance of economic transactions. Following Polanyi, we distinguish three governance mechanisms of economic relations and note that, to be operational, each of them requires a different social structure and social regulation. (English)
Keywords: economic activity; economic sociology; ekonomska sociologija; governance mechanisms; institutional economics; international economic relations; mehanizmi upravljanja; social structure; socioeconomics

An Analytical Framework for the Relationship between Environmental Measures and Economic Growth Based on the Regulation Theory: Key Concepts and a Simple Model - Okuma, Kazuhiro (Evolutionary and Institutional Economics Review, 2012)
This paper proposes an analytical framework using the regulation approach and consisting of explanations of some concepts and a simple way of modeling; the concepts and modeling are developed by focusing on the distributive aspect of environmental issues and using environmental costs as key indices. As a basis for the framework, we refer to the ideas of Polanyi and the surplus approach, and we recognize the socio-economic system as interlinked triple reproductions of the economy, humans, and the environment. This recognition is formalized as an equation of three-dimensional distributions among profits, wages and rents. The "economy-environment nexus," which represents the relationship between the natural environment's reproduction and economic reproduction, is analyzed as one of the institutional forms. The dynamics of institutional coordination are specified with attention to distributive conflicts between relevant actors, leading to the idea of "spatial and temporal gaps of coordination." Environmental costs are identified and incorporated into the equation of distribution as key information to characterize specific forms of the economy-environment nexus. The economy-environment nexus influences growth regimes through multiple routes, including investment, trade, and productivities. In order to analyze the aggregate effects, we propose a variant of the Kaleckian growth model incorporating environmental costs as key variables. Using this model, we specify conditions for the "paradox of costs for environmental measures," where environmental measures raise the profit rate. This framework is expected to be used in historical or comparative analyses of particular economies, including those using periodized specification of the economy-environment nexus.
Keywords: Marxian; Sraffian; current heterodox approaches: socialist; distributional effects; employment effects; environment and development; environment and growth; environment and trade; environmental accounts and accounting; environmental equity; pollution control adoption costs; population growth; sustainability

China's Decentralized and Inegalitarian Developmental State - Nordhaug, Kristen (Forum for Development Studies, 2012)
This article investigates China's market reforms and rapid economic development from the late 1970s. The following questions are posed: (1) How did the Chinese 'peasant revolution' and the rural policies and institutions of Mao China influence the market reforms and subsequent economic development? (2) How does China's development after the market reforms relate to Marxist and Polanyian notions of proletarization and commodification of land and labour as preconditions of capitalist development? (3) To what extent and why does China's development after the market reforms diverge from East Asian growth with equity? (4) How does China's 'decentralized developmental state' influence its growth model and distribution? (5) The present Chinese government tries to promote greater equality and more domestic consumption. Is this a Polanyian 'double movement' in response to commodification of land and labour? How likely are these policies to succeed? These questions are addressed through historical-comparative analyses with comparisons of long-term rural dynamics of Mao China and the former Soviet Union. China after the market reforms is compared with England during its transition to agrarian capitalism and industrial capitalism from the sixteenth century through the early nineteenth century and with Taiwan and South Korea from the late 1940s until the 1980s.
Keywords: Marxian; Sraffian; aggregate factor income distribution; current heterodox approaches: socialist; inflation; institutions and growth; institutions: design, formation, and operations; macroeconomic analyses of economic development; money; socialist systems and transitional economies: national income, product, and expenditure; structure, scope, and performance of government

As especificidades da mercadoria força de trabalho: Marx revisitado - Antonio Vieira, Pedro (The specifities of the labor power commodity: Marx revisited (the labor power commodity: Marx revisited., 2012)
Coming along with Polanyi's ideas of fictitious commodity, this paper seeks to reveal the logical inconsistencies and silents in the economic science arguments on the labor force as a commodity. Once Marx's influence on the anti-capitalist movements is outstanding, we need to show his contribution, through his economic thought, to the scientific economism. As is well known, when proposed that the commodity sell by the worker was the 'labor force' instead the labor, as the classical economists used to say, Marx was able to built his theory on the capitalist economy theory, which relies on the concept of surplus value.. That is the reason why the paper is specially concern with the failures or weaknesses present in one of the huge Marx contribution to the economics thought: the concept of labor force. (English)
Keywords: MARX, Karl, 1818-1883; anti-globalization movement; capitalists & financiers; commercial products; economics; economism; economists; fictitious commodities; labor force; labor supply; labor-market; labour force; labour market; labour supply; political economy

L'idéologie marchande au service de la biodiversité ? - Tordjman, Hélène; Boisvert, Valérie (Mouvements, 2012)
Keywords: biodiversity; markets

Retour sur le désencastrement - Brisset, Nicolas (Revue européenne des sciences sociales. European Journal of Social Sciences, 2012)
Our ambition is to point out that a fresh look at what is usualy considered to be Karl Polanyi’s magnum opus, The Great Transformation, opens some new prospects on its analytical. This interpretation qualifies some of the Hungarian author’s main critics, directed against his concept of desembeddedness. With this aim in mind, we re-interpret this debate in epistemological terms, i.e. the link between concepts and reality ; then we try to connect Karl Polanyi with the notion of performativity, which is today flourishing, above all within the field of economic sociology.
Keywords: Great Transformation, The (Book); Karl Polanyi; disembeddedness; great transformation; performativity; realism

Crise ? Vous avez dit : « Crise » ? - Naszályi, Philippe (Revue des Sciences de Gestion, 2012)
Crisis and institutional environment, crisis and organisational anticipations and crisis and consumer behaviour, just a few of the uses of the word « crisis » ; a word which, for over four years now, for the less perspicacious, and for over thirty years, for those who have been watching the bigger picture, has been the most appropriate word for this stage of development of the contemporary economic system. But exactly « what crisis are we talking about? ». That which is the result of a system, of an ideology which inhabits this system and of which the slightest of abilities was to try and present itself as unable to be exceeded, « by the end of the story ».' Yet, just as Max Weber stated, it seems that today's knowledge is still destined to be exceeded, particularly in the humanities, since society is constantly undergoing transformation. There is, therefore, no economic model which should not be discussed in order to be improved, or replaced. By delving into the ideal of Sismondi, today wrongfully forgotten, or in studying Karl Polanyi, we can gain much support for contemporary reflection which cannot continuously oppose Keynes, often summarised to the deficit of public policies and the « Chicago Boys » of which the action with Augusto Pinochet is truly symbolic of this « neo-liberalism» of American conservatives which is spreading across the globe, despite the crises which it has created. Crisis? Did you say: « Crisis' ? A question, and observation, but also in the manner of «great thinkers », solutions and alternatives which managers, in the widest sense of the term, « those who look after others and their businesses », provide through thirteen articles, collated into three thematic sections in this Spring edition which opens up new areas for reflection and action as « it is indeed time to put production before speculation, future investment before current satisfaction, sustainable employment before immediate profiteering ». (English)
Keywords: WEBER, Max, 1864-1920; consumer behavior; economic models; economic systems; humanities; institutional environment

Textos escogidos. Karl Polanyi - Coraggio, J.L. (Buenos Aires : Consejo Latinoamericano de Ciencias Sociales (CLACSO) ; Los Polvorines, Provincia de Buenos Aires : Universidad Nacional de General Sarmiento, 2012)
Contents of book: Primera parte: Karl Polanyi y su obra: Actualidad de Karl Polanyi / Jean-Louis Laville. Karl Polanyi : su vida y época / Marguerite Mendell y Kari Polanyi Levitt. Karl Polanyi y la otra economía en América Latina / José Luis Coraggio -- Segunda parte: Los ensayos de Karl Polanyi: El lugar de las economías en las sociedades (1957) ; La economía como proceso instituido (1957) ; Aristóteles descubre la economía (1957) ; Feudalismo primitivo y feudalismo de la decadencia (1950) ; Marxismo e historia económica (comentario a Maurice Dobb) (1947) ; Comerciantes y comercio (1951) ; Semántica de los usos de la moneda (1957) ; Economía y democracia (1932) ; La esencia del fascismo (1935). El fascismo y la terminología marxista (1934) ; El marxismo redefinido (1934) ; Marx sobre el corporativismo (1934-1937) ; El cristianismo y la vida económica (1934-1937) ; Comunidad y sociedad : la crítica cristiana a nuestro orden social (1937) ; ¿Capitalismo universal o planificación regional? (1945) ; El significado de la democracia parlamentaria (1944-1945) ; Nuestra obsoleta mentalidad de mercado (1947) ; Sobre la creencia en el determinismo económico (1947) ; Jean-Jacques Rousseau o ¿Es posible una sociedad libre? ; La libertad y la tecnología (1955) ; La máquina y el descubrimiento de la sociedad (1957) ; La libertad en una sociedad compleja (1957) ; La sociedad opulenta según Aristóteles (1959).
Keywords: antropología económica; economic anthropology; economic history; economics; economía; historia económica

The Fundamental and Eternal Conflict - Parguez, Alain (International Journal of Political Economy, 2012)
This contribution aims at exploring what is today the new "normal" in economic policy, namely, austerity. It must be read as a homage to Karl Polanyi, the first who understood the tragedy, and to Kari Polanyi-Levitt, who expanded on her father's thought. Austerity has nothing to do with old anticyclical or stabilizing policies. It is a permanent regime devoid of any sound foundations. It is a pure quasi-religious policy that is self-reinforcing. The author emphasizes the fundamental conflict between its promoter, Friedrich Hayek, and its adversary, John Maynard Keynes, and points to the sole towering intellectual, Karl Polanyi, who understood that their conflict embodied two radically different visions of the world. Polanyi discovered that the core of the conflict was the merciless fight between the supreme rule of God-given market laws, the Hayekian order, and democracy enshrined in a peaceful society that is oriented toward the future. The Hayekian order abolishes the modern democratic state, sacrifices the future, and extols poverty for the sake of order. Polanyi was the first to have discovered the true message of Keynes, who had destroyed the logical foundations of Hayek's philosophy and economics. In conclusion, the author strives to explain why, early in the twenty-first century, the Hayekian legacy is the true road to serfdom because it ignores Polanyi and encourages belief in market laws. Early American "Keynesians," who knew nothing about Hayek, transformed Keynes into a new Léon Walras. These early Keynesians were doomed from the start and vanished when they endorsed the Philips curve as expressing the absolute truth.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; KEYNES, John Maynard, 1883-1946; Keynesian economics; The General Theory of Employment, Interest & Money (book); austerity; banking industry -- Social aspects; consumption (economics); economic history; employment (economic theory) - social aspects; equilibrium (economics); flexibility; free enterprise; government policy; history of economics - 20th century; international political economy; investments - social aspects; market laws; mixed economy - social aspects; money; money - social aspects; scarcity - social aspects; state

Critique of Current Neoliberalism from a Polanyian Perspective-Politics, Philosophy, and Economics - Seccareccia, Mario (International Journal of Political Economy, 2012)
An introduction is presented which discusses articles within the issue on topics including neoliberalism, the Austrian economist Karl Polanyi's perspective on the history of industrial society during the nineteenth and twentieth centuries and free enterprise.
Keywords: POLANYI, Karl, 1886-1964; free enterprise; neoliberalism; political economy

The Belief in Economic Determinism, Neoliberalism, and the Significance of Polanyi's Contribution in the Twenty-First Century - Thomasberger, Claus (International Journal of Political Economy, 2012)
How can we explain why Karl Polanyi's book The Great Transformation is more relevant today than ever before? The central thesis of the paper is that Polanyi's analysis is groundbreaking because it goes far beyond the interpretation of the civilization of the nineteenth century. By focusing on the "belief of economic determinism," Polanyi challenges the juxtaposition of being and thinking, of material life-process and consciousness. He rejects the assumption that society encompasses a world of objective facts independent of theoretical beliefs and visions. Polanyi's work is of utmost importance today because by anticipating a change in approach such as the liberal authors made, from the opposite point of view, during the interwar period, he offers the key not only to the analysis of the market mechanism, but also to a critical understanding of neoliberalism.
Keywords: Austrian school; Austrian school of economics; Great Transformation, The (Book); Keynesian economics; Marxist philosophy; POLANYI, Karl, 1886-1964; belief & doubt - social aspects; central economic planning - social aspects; double movement; economic determinism; economic history - 19th century; economic planning; economic theory; fictitious commodities; free enterprise - social aspects; history of economics - 20th century; human behavior - economic aspects; laissez-faire; neoliberalism; neoliberalism - social aspects; self-fulfilling prophecy; socioeconomics; utopias - economic aspects